The boy who dared - Bartoletti, Susan Campbell (Scholastic Press, 2008)
In October, 1942, seventeen-year-old Helmuth Hübener, imprisoned for distributing anti-Nazi leaflets, recalls his past life and how he came to dedicate himself to bring the truth about Hitler and the war to the German people.